Genetic Overlap of Schizophrenia and Bipolar Disorder in a High-Density Linkage Survey inthe Portuguese Island Population - Fanous, Ayman H. (2017)
Recent family and genome-wide association studies strongly suggest shared genetic risk factors for schizophrenia (SZ) and bipolar disorder (BP). However, linkage studies have not been used to test for statistically significant genome-wide overlap between them. Forty-seven Portuguese families with sibpairs concordant for SZ, BP, or psychosis (PSY, which includes either SZ or psychotic BP) were genotyped for over 57,000 markers using the Affymetrix 50K Xba SNP array. NPL and Kong and Cox LOD scores were calculated in Merlin for all three phenotypes. Empirical significance was determined using 1,000 gene-dropping simulations. Significance of genome-wide genetic overlap between SZ and BP was determined by the number of simulated BP scans having the same number of loci jointly linked with the real SZ scan, and vice versa. For all three phenotypes, a number of regions previously linked in this sample remained so. For BP, chromosome 1p36 achieved significance (11.54-15.71 MB, LOD = 3.51), whereas it was not even suggestively linked at lower marker densities, as did chromosome 11q14.1 (89.32-90.15 MB, NPL = 4.15). Four chromosomes had loci at which both SZ and BP had NPL ≥ 1.98, which was more than would be expected by chance (empirical P = 0.01 using simulated SZ scans; 0.07 using simulated BP scans), although they did not necessarily meet criteria for suggestive linkage individually. These results suggest that high-density marker maps may provide greater power and precision in linkage studies than lower density maps. They also further support the hypothesis that SZ and BP share at least some risk alleles.